Cyclostationarity in communications and signal processing - Gardner, William A. (IEEE Press, 1994)
"By providing a comprehensive collection of contributions on the history and current state of the art in this rapidly emerging field, this book gives you a complete survey of the theory, applications, and mathematics of cyclo-stationarity. It brings together the latest work in the field by the foremost experts and presents it in a tutorial fashion." "From this book, you will learn new concepts, methods, and algorithms for performing signal processing tasks and designing and analyzing communications systems." "Cyclostationarity in Communications and Signal Processing features both broad chapters and more narrowly focused articles that provide in-depth surveys reviewing the newest developments in specific areas. The tutorial style, coupled with the comprehensive reference lists that are provided, make this book instrumental in furthering progress in understanding and using cyclostationarity in all fields where it arises."--BOOK JACKET.